Because of the rabbit - Lord, Cynthia (New York : Scholastic Press, 2019)
On the last night of summer, Emma and her Maine game warden father rescue a small domestic rabbit stuck in a fence; the very next day Emma starts fifth grade after years of being home schooled, excited and apprehensive about making new friends, but she is paired with Jack, a hyperactive boy, who does not seem to fit in with anyone--except that they share a love of animals, which draws them together, because of the rabbit.
Keywords: Rabbits -- Juvenile fiction; Schools -- Juvenile fiction; Home schooling -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Maine -- Juvenile fiction; Rabbits -- Fiction; Schools -- Fiction; Home schooling -- Fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; Family life -- Maine -- Fiction; Maine -- Juvenile fiction; Maine -- Fiction